The African Genomic Medicine Training Initiative (AGMT): Showcasing a Community and Framework Driven Genomic Medicine Training for Nurses in Africa - Nembaware, Victoria; , African Genomic Medicine Training Initiative; Mulder, Nicola; Abidi, Omar; Akanle, MB; Ali, Stuart Alvaro; Aliga, Cliff Asher; Chauke, Paballo; Cotzee, Minnet; Dandara, Collet; Fadlelmola, Faisal M.; Fawale, Michael B.; et al. (Frontiers in Genetics, 2019)
The potential of genomic medicine in improving the quality of healthcare both at population and individual-level is well-recognised globally. However, successful adoption of genetic and genomic evidence into clinical practice depends on training the healthcare workforce and clinical researchers in genomic medicine. Due to limited expertise in the medical genetics and genomics field, widespread uptake largely depends on task-shifting for the implementation of genomic medicine implementation to key healthcare professionals such as nurses. Their knowledge would be developed through courses aimed at professional development. Globally, trainers, and training initiatives in genomic medicine are in early stages of development, but resource limited settings such as the African continent face additional logistical and institutional challenges. The African Genomic Medicine Training (AGMT) Initiative was conceived during a combined conference of the African Society of Human Genetics (AfSHG) and the Human Heredity and Health in Africa Consortium (H3Africa) in 2016, Senegal, in response to the needs for developing knowledge and skills in genomic medicine. AGMT was established to implement a sustainable genomic medicine training initiative primarily for healthcare professionals who are not geneticists but are nurses, doctors and pharmacists in Africa. This paper reports on the establishment of the AGMT initiative and the strategies developed and piloted by this initiative in designing and implementing an accredited frame-work and community-based blended learning course for nurses across 11 African countries. The global implementation experiences, outcomes and lessons learnt are highlighted. The AGMT initiative strategy takes advantage of existing research consortia and networks to train and create a pool of trainers and has adopted evidence-based approaches to guide curriculum and content development/adaptation. This initiative established the first Africa-wide online blended learning genomic medicine course which forms the basis from which to develop courses for other healthcare professionals and the wider public.